Polymorphisms of BDNF Gene and Autism Spectrum Disorders: Family Based Association Study with Korean Trios - Yoo, Hee Jeong (Korean Neuropsychiatric Association, 2014)
OBJECTIVE: Autism spectrum disorders (ASDs) are a group of early childhood-onset neurodevelopmental disorders characterized by deficits in social interaction and language skills, and repetitive behaviors. Brain-derived neurotrophic factor (BDNF) plays a critical role in the differentiation of normal neuronal cells during embryonic and postnatal neuronal development through its neurotrophic effects. METHODS: In this study, we performed a family-based association test (FBAT) between single nucleotide polymorphisms (SNPs; rs6265, rs11030101, rs7103411, and rs7103873) or haplotypes in the BDNF gene and affection status or several quantitative traits characterized by ADI-R with151 Korean trios, including a child diagnosed as ASDs. RESULTS: While no significant association was found between SNPs or haplotypes and the ASDs disease status, a quantitative transmission disequilibrium test (QTDT) by using quantitative traits identified associations of the SNPs (rs6265 and rs11030101) with a domain score for "Restricted, Repetitive and Stereotyped patterns of behavior" (C domain), especially at the subdomain scores for "encompassing preoccupation or circumscribed pattern of interest" (C1) (rs6265A allele, dominant model, p-value=0.019; rs11030101 A allele, additive model, p-value=0.015) and "preoccupations with part of objects or non-functional elements of material" (C4) (rs11030101 A allele, additive model, p-value=0.015) within the ADI-R diagnostic algorithm. In addition, significant associations were also identified between the haplotypes and these quantitative traits (C1, p-value=0.016; C4, p-value=0.012). CONCLUSION: We conclude that BDNF gene polymorphisms have a possible role in the pathogenesis of ASDs.